THE DEVELOPMENT OF BIOLOGY PRACTICE IN HIGH SCHOOL SCHOOL BASED ON ‎ETHNOBIOLOGY - Siti Sunaryati; suatma suatma suatma; Yula Miranda‎ (EDUSAINS, 2017)
Local knowledge of the Dayak Ngaju community in Gunung Mas regency, Central Kalimantan there were believed that many species of plants, animals and their surroundingscan be used as an indicator of a particular environtment. The local people experience is one example of local knowledge which needs to be studied scientifically through ethnobiology.Study of ethnobiology was confined to the local community's knowledge about the medicinal plants (ethnobotany), local community knowledge about the utilization of existed nearby animals (ethnozoology) and knowledge of the local community in ecosystems around their living quarters (ethnoecology). Afterwards these studies was arranged into biology practical work material. The purposesof the studyare(1) to study theethnobiology of local knowledge of DayakNgajucommunitiesinGunung Mas regency, (2) to inventoryandidentifyseveral species that areusedin foodstuffs, pharmaceuticals, industry and utilization of the environment for the practical work in high school. This should be well documented and to be taught to the next generations to avoid the extinction of local knowledges.Integratingthe materialethnobiology into learningbiology is one of the best ways to deliverlocalknowledge in formal education. It was suggested to teach ethnobiology inbiology practical work, especially inhigh school who have forest environment as characteristic oftheir territory since ethnobiological material was very important. Keywords:ethnobiology; practical work;high school.